A new approach to second language teaching - Sizemore, Mamie; Arizona State Dept. of Public Instruction, Phoenix ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1962)
This is an up-dated edition of Arizona state Department of Education's 1939 "instruction of bilingual children" publication. Its purpose is to present the principles of modern linguistic science as they relate to teaching English as a second language. Areas covered include the problems of bilingual children, importance of a friendly classroom climate, cultural conflicts in teaching Indian children, curriculum overviews, including language arts, mathematics, science, and social studies, the role of the linguist in the classroom, an overview of teaching English as a second language, and comparisons between English and the navaho and Spanish languages. Reference materials are included for teachers of English as a second language. The editor states that the ideas and problems presented are common to other minority groups. (rb)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acculturation; American Indians; Bilingual Students; Education; English (Second Language); Instruction; Instructional Materials; Language; Linguistics; Navajo; Spanish; Spanish Americans; Arizona (Phoenix)